A Cultural History of Medicine Middle Ages (800 - 1450) [volume 2] (Bloomsbury Academic, 2021)
How has our understanding of medicine evolved over the past 2,500 years? A Cultural History of Medicine, as the first comprehensive and interdisciplinary overview of the cultural history of medicine from ancient times to modernity, discusses this. With six highly illustrated volumes covering 2500 years of human history, this is the definitive reference work on the subject.
English
Keywords: History of medicine; history of medicine